2019
DOI: 10.1002/ecs2.2599
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences resource use by chestnut‐bellied scaled quail

Abstract: Animals use physiological and behavioral adaptations to maintain constant body temperatures when environmental temperatures are outside of their thermoneutral zone. We define the temperature suitability bounds as the range of temperatures above and below which animals avoid locations because of unfavorable thermal conditions. Temperatures outside the temperature suitability bounds may trigger behavioral responses such as movement to cooler locations. We tested the hypothesis that temperature during late April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Authors characterizing temperatures by bobwhite in the literature commonly report estimates of operative temperature by using temperature loggers fixed inside black, steel spheres (Carroll et al., 2015, 2016, 2018; Kline et al., 2019; Olsen et al., 2018). Operative temperatures represent the temperature experienced by an animal by accounting for solar radiation and convection.…”
Section: Methodsmentioning
confidence: 99%
“…Authors characterizing temperatures by bobwhite in the literature commonly report estimates of operative temperature by using temperature loggers fixed inside black, steel spheres (Carroll et al., 2015, 2016, 2018; Kline et al., 2019; Olsen et al., 2018). Operative temperatures represent the temperature experienced by an animal by accounting for solar radiation and convection.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical obstruction, or vertical cover of woody vegetation, was associated with reduced ground surface temperatures during early afternoon on our study sites (Kline et al 2019). Kline et al (2019) reported that vertical cover influenced relative probability of selection by scaled quail more strongly than shrub canopy cover. Shrubs are also important to scaled quail for nesting.…”
Section: Discussionmentioning
confidence: 66%
“…Scaled quail in Oklahoma and New Mexico, USA, likewise selected locations with overhead cover and a sparse herbaceous understory (Schemnitz , Campbell et al ). In addition to a more open understory, shrubs provide other resources such as protection from predators (Schemnitz ) and more moderate temperatures (Guthery et al , ; Kline et al ). Vertical obstruction, or vertical cover of woody vegetation, was associated with reduced ground surface temperatures during early afternoon on our study sites (Kline et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation